2012
DOI: 10.1021/la300831p
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy Nanoassembly of Polyelectrolyte and Layered Clay Multicomposite toward a Reliable Gas Barrier

Abstract: Flexible and transparent gas-diffusion barriers have played an important role in recent years. The present study describes a flexible barrier film with a tailored architecture of cationic polyelectrolytes and clay/polymer nanoassemblies. Highly oriented and well-aligned barrier films were achieved by the consecutive absorption of flexible cationic polymer and anionic montmorillonite platelets. The experimental results showed that the layer-by-layer deposition of oppositely charged thin films containing self-as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 25 publications
0
29
0
Order By: Relevance
“…Cellulose nanofiber/clay nacre‐like layered nanocomposites films have also been reported to show excellent gas‐barrier properties . Another typical gas‐diffusion barrier MTM/PVA composite for preventing water permission was reported by Choi et al, which showed a water‐vapor transmission value of 5.6 × 10 −3 g m −2 day −1 at 20 °C …”
Section: Applications Of Nacre‐inspired Materialsmentioning
confidence: 94%
“…Cellulose nanofiber/clay nacre‐like layered nanocomposites films have also been reported to show excellent gas‐barrier properties . Another typical gas‐diffusion barrier MTM/PVA composite for preventing water permission was reported by Choi et al, which showed a water‐vapor transmission value of 5.6 × 10 −3 g m −2 day −1 at 20 °C …”
Section: Applications Of Nacre‐inspired Materialsmentioning
confidence: 94%
“…An improvement of the exposure time is the appearance of layer-by-layer assembly (LBL) technique [105]. Shi et al [106] used LBL technique on a pure Ti surface as a delivery system and showed the coating with controlled release of multilayer antibiofilm peptides decreased the growth of both Gram-positive ( Staphylococcus aureus ) and -negative ( P .…”
Section: Antibiofilm Peptide Applications In Periodonticsmentioning
confidence: 99%
“…Figure 7c shows the presence of platelets of MMT tactoids in which the dark lines were the intersection of MMT layers. Choi et al [45] reported this type of observation. These results indicated well incorporation of MMT in the nanoparticles.…”
Section: Morphology Study Of the Nanoparticlesmentioning
confidence: 60%